2022
DOI: 10.3389/fimmu.2022.922780
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis of cuproptosis-related gene in triple-negative breast cancer

Abstract: BackgroundCuproptosis is a copper-dependent cell death mechanism that is associated with tumor progression, prognosis, and immune response. However, the potential role of cuproptosis-related genes (CRGs) in the tumor microenvironment (TME) of triple-negative breast cancer (TNBC) remains unclear.Patients and methodsIn total, 346 TNBC samples were collected from The Cancer Genome Atlas database and three Gene Expression Omnibus datasets, and were classified using R software packages. The relationships between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 62 publications
0
59
0
Order By: Relevance
“…Many studies have applied CRGs to predict outcomes and guide treatments for cancer patients, for example, triple-negative breast cancer, hepatocellular carcinoma, and bladder cancer patients. As shown in previous studies, CRGs are closely related to the prognosis of breast cancer patients (Sha et al, 2022). In addition, the cuproptosis-related risk score could divide liver cancer patients into two groups with differences in mutation status and responded to target therapy in different ways (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 80%
“…Many studies have applied CRGs to predict outcomes and guide treatments for cancer patients, for example, triple-negative breast cancer, hepatocellular carcinoma, and bladder cancer patients. As shown in previous studies, CRGs are closely related to the prognosis of breast cancer patients (Sha et al, 2022). In addition, the cuproptosis-related risk score could divide liver cancer patients into two groups with differences in mutation status and responded to target therapy in different ways (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 80%
“…The cuproptosis-related risk profiles for lncRNA may aid in determining the prognosis and molecular profile of patients with ccRCC, lung adenocarcinoma, and hepatocellular carcinoma as well as improving therapy choices that may be used in the clinic [40][41][42]. According to the current study, a novel signature based on the cuproptosis gene may be able to predict a patient's prognosis, biological makeup, and the best course of therapy for them if they have glioma or triple negative breast cancer [43,44]. The immune microenvironment and tumor immunotherapy may both be affected by cuproptosis-related lncRNAs at the same time [45][46][47].…”
Section: Discussionmentioning
confidence: 89%
“…In this work, we rst implemented the functional enrichment of 10 cuproptosis genes in BRCA. We found that most of these genes are involved in biological processes 'acetyl-CoA biosynthetic process from pyruvate', 'mitochondrial acetyl-CoA biosynthetic process from pyruvate' and 'tricarboxylic acid cycle', which are all closely linked to the development of BRCA (23). We discovered that of the 10 cuproptosis genes, CDKN2A and PDHB expression were dramatically increased in BRCA samples as compared to normal samples, but the expression of the other genes was signi cantly decreased.…”
Section: Discussionmentioning
confidence: 91%